Diálogos Atemporais de Música e Imagem: Ressignificando a obra de Clemente Ferreira Júnior (1864-1917) - VENTURIERI, Leonardo Vieira (Universidade Federal do Pará, 2023)
In the present thesis, ‘Timeless dialogues between music and image: resignifying Clemente Ferreira Júnior’s work (1864-1917)’, the author aims to promote a dialogue between Clemente Ferreira Júnior’s work (his great grandfather), composer, pianist and conductor, with his own work, considering epistemologies in the study of music and image. The author presents a historical summary, presenting an overview of the composer’s sociocultural surroundings, subsequently making an analysis of his pianistic work, utilizing an semiologic and semiotic perspective (musical and visual), aiming do unveil creative (poietic) and perceptive (estesic) aspects, considering its covers, the musical object and a few historical aspects. Develops, therefore, a musical product as a result of the epistemological and phenomenological dialogue, the Imaginary landscapes catalog, throughout artistic and compositional processes (“transmelodies” e “pictoscores”), transforming and resignifying Clemente’s work, to be released in parallel as this thesis. The author aimed to establish, therefore, a transdisciplinary artistic and epistemological dialogue, combining musical semiology and semiotics, proposing an outline for a kinesthetic sign, grounded in different notions from various authors: Nattiez (1990), Molino (1990), Tarasti (1994).